Prospective Diagnosis and Treatment of Pandas - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Twelve school-aged children with new-onset pediatric autoimmune neuropsychiatric disorder with group A streptococcal infection (PANDAS) were identified over a 3-year period (1998-2000) at the University of Rochester, NY.